Forest Rights Act - a Conservation Tool - Jha, Arvind Kumar (Indian Forester, 2009)
Just one amongst the thirteen forest rights mentioned in the Scheduled Tribes and Other Forest Dwellers (Recognition of Forest Rights) Act 2006 relates to the recognition of forest right in the form of the right to hold and live in the forest land for habitation or for selfcultivation for livelihood. This Act however, has not been properly understood by a large section of society. The preamble, however, read together with all the provisions contained in the Act and Rules reveals the real face of the Act. A proactive approach of foresters towards the implementation of this Act in its entirety has the potential to make this Act emerge as a conservation document. The perspective is based on the experience gained in the implementation of the Forest Rights Act in the state of Maharashtra.